VD_FINDINFO HC / 2010 / 555 vom 20. Juli 2010 - VD Tribunal cantonal (2010)
CONTRAT DE TRAVAIL, FAUTE LÉGÈRE, RESPONSABILITÉ CONTRACTUELLE, TRAVAILLEUR | 321e CO, 343 al. 3 CO, 97 CO, 99 al. 3 CO, 444 CPC, 445 CPC, 451 CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 465 al. 1 CPC, 471 al. 3 CPC, 10 LJT, 46 al. 2 LJT, 46 LJT